Structural chemistry of Ln(2)BaLiRuO(7) (Ln = La, Pr) - Battle, P; Grey, C; Rodgers, J; Sloan, J (2006)
Polycrystalline samples of the n=2 Ruddlesden-Popper compositions Pr 2BaLiRuO7 and La2BaLiRuO7 have been synthesised by solid-state techniques and characterised by X-ray and neutron diffraction, electron microscopy and 7Li MAS NMR. The 6-coordinate sites are occupied by a 1:1 ordered arrangement of Li and Ru, the 12-coordinate sites within the perovskite-like blocks are occupied by Ba, and the cation sites on the block edges are occupied by La or Pr. Although the cation ordering is maintained within each block, stacking faults occur on passing between neighbouring blocks; the concentration of stacking faults is greater for Ln = La. © 2006 Elsevier SAS. All rights reserved.